A 4/spl times/4 space dilated lightwave network - reducing crosstalka new approach - Suliman, F. M.; Mohammad, Abu Bakar; Seman, K. (2002)
Abstract: In this paper, the space dilation concept for reducing crosstalk in Ti:LiNbO/sub 3/ directional-coupler-based photonic switches operating at a single wavelength is applied using a new approach. A new method for minimizing the switch crosstalk is described A novel 4/spl times/4 switch architecture is proposed for nonblocking photonic switching networks to fully exploit the advantages of this method. Some properties of the switch architecture are derived and analyzed. The performance of the switch is also discussed and compared with other well-known network architectures.